Strategi Komunikasi Pemasaran Wisata Baru Setigi di Gresik Jawa Timur - Jannah, Uzlifatul; Moh. Moefad, Agoes (Jurnal Ilmu Komunikasi, 2019)
This article discusses how the tourism marketing communication strategy "Setigi" in Sekapuk Village, Ujungpangkah District, Gresik Regency. The purpose of this study was to determine the marketing communication strategy of Village-Owned Enterprises (Bumdes) and tourism awareness groups (Pokdarwis) "Pelangi" in tourism marketing. limestone hill "Setigi" to attract visitors. This study uses a qualitative-descriptive approach based on integrated marketing communication theory. The result of this research is the implementation of a marketing communication strategy carried out by Bumdes and Pokdarwis "Pelangi" in Sekapuk Village, Ujungpangkah District, Gresik Regency utilizing social media and collaborating with the youth community in the Gresik area, as well as collaborating with the Gresik Regency Tourism Office